2003
DOI: 10.1128/mcb.23.2.566-578.2003
|View full text |Cite
|
Sign up to set email alerts
|

T-Cadherin-Mediated Cell Growth Regulation Involves G2 Phase Arrest and Requires p21CIP1/WAF1 Expression

Abstract: Members of the cadherin family have been implicated as growth regulators in multiple tumor types. Based on recent studies from our laboratory implicating T-cadherin expression in mouse brain tumorigenesis, we examined the role of T-cadherin in astrocytoma growth regulation. In this report, we show that T-cadherin expression increased during primary astrocyte physiologic growth arrest in response to contact inhibition and serum starvation in vitro, suggesting a function for T-cadherin in astrocyte growth regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 66 publications
5
59
1
1
Order By: Relevance
“…34 Western blot analysis of 2 panels of human GBM cell lines confirmed that CDH1 expression was rare as it is often replaced by CDH13. 35 In GBM cells, overexpression of CDH13 suppresses proliferation and migration, 36 consistent with our observations in nude mice. In addition, we found that MIR517C overexpression suppressed CDH13, suggesting that MIR517C inhibited EMT signals to affect CDH13 transcription.…”
Section: Discussionsupporting
confidence: 79%
“…34 Western blot analysis of 2 panels of human GBM cell lines confirmed that CDH1 expression was rare as it is often replaced by CDH13. 35 In GBM cells, overexpression of CDH13 suppresses proliferation and migration, 36 consistent with our observations in nude mice. In addition, we found that MIR517C overexpression suppressed CDH13, suggesting that MIR517C inhibited EMT signals to affect CDH13 transcription.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we demonstrated that T-cadherin had antiproliferative effects and antitumorigenic roles in HCC cells. These findings were consistent with those of previous studies on other cancer cell types 5,26,27 and suggest that T-cadherin may have different and perhaps opposite roles in epithelial and endothelial cells. Although the antitumorigenic roles of T-cadherin have been documented in a number of human cancer cell types, 5,26,27 the molecular mechanisms are unclear.…”
Section: Discussionsupporting
confidence: 83%
“…4a). Since previous studies have shown that T-cadherin induced G 2 /M arrest in gliomas and cutaneous squamous carcinoma, 26,27 we examined the cell cycle changes of T-cadherin-stable transfectants with flow cytometric analysis. After cell synchronization with serum-free treatment, we found that all T-cadherin transfectants of PLC/PRF/5 (C5 and C8) had higher proportions of cells at the G 2 /M phase than their vector controls (Fig.…”
Section: T-cadherin Induced G 2 /M Cell Cycle Arrestmentioning
confidence: 99%
“…3). Interestingly, T-Cadherin, a member of the family devoid of the intracellular moiety, is expressed exclusively in the basal cells of the skin 53,54 and down-modulated in psoriatic skin. 55 Recent profiling experiments with TAp63 identified several pro-apoptotic targets.…”
Section: Discussionmentioning
confidence: 99%